Strict convexity of the upper level sets of strictly quasiconcave functions - Danao, Rolando A. (The Philippine Review of Business and Economics, 1990)
This paper shows that a necessary condition for strict quasiconcavity is that each level set is contained in the boundary of the associated upper level set. This condition and the strict convexity of upper level sets are sufficient for strict quasiconcavity and are also necessary when the function is continuous with a strict convex domain.